Policy Space Index : Short-Term Response to a Catastrophic Event - Ferrer, Jose (IMF Working Papers; Working Paper, 2022)
What policy space does a country have for a short-term response to a catastrophic event? To quantify this space, the paper proposes a policy space index. The index combines a quantitative, albeit relatively limited and narrow, fiscal space concept with the indicators of nominal monetary space and reserve space. Each nominal policy space indicator is then adjusted for individual country's institutional features, such as the status of its currency, income group, access to capital markets, debt distress level, and the exchange rate regime. The final policy space index is derived as a composite of the three nominal policy space indicators, each adjusted for five institutional features. This index is different from the approach to measure fiscal space at the IMF and requires more work before it can be used operationally. The proposed index allows measuring the overall policy space in each country directly in percent of GDP. By way of illustration, the paper applies the index to the Covid-19 crisis.